The Individual and the «Spiritual» World in Kafka's Novels - Ulrich Fülleborn (Studies in 20th & 21st Century Literature, 1978)
Following an earlier essay by the same author on 'Perspektivismus und Parabolik' in Kafka's shorter prose pieces, this article gives a description of the structure of Kafka's novels in terms of the concepts 'the individual' (cf. Kierkegaard's 'individuals') and 'the spiritual world' (Kafka: «There is no world but the spiritual one»). Joseph K. and the land-surveyor K. become individuals by leaving the world of everyday life and passing over into the incomprehensible spiritual world of trials and a village-castle community, in the same way that Karl Rossmann had passed over into the 'Nature-theatre of Oklahoma' before them. And they remain as individuals, since in this world they struggle to hold their own. As they can only employ their intellect as an excessive mania for calculation in this struggle, any interpretation of the novels must end in the seemingly unanswerable question: how can such a struggle lead, on the one hand, to a free and rational form of existence and, on the other, to some form of relatedness with those strange spiritual worlds? This question has a direct bearing on the main conclusion of this essay, namely that the role of the parable becomes more and more important from one novel to the next: that is to say, the spiritual world attains universal validity for Kafka and proves to be the only world where life has any meaning.
Keywords: Franz Kafka; novels; spiritual world; spiritual